Karakteristik Tabung Udara Pada Pompa Hidram - Muhamad Jafri (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2018)
The purpose of this paper is to provide the fact that the air tube of a hydram pump. The method used in making this paper is to collect several published research articles on the effect of using an air tube on a hydram pump. The data obtained were analyzed to get air tube water on the hydram pump. The results of the analysis show that the use of an air tube has a good effect on improving the performance of the hydram pump. The greater the volume of the air tube, the higher the discharge air and the higher the pump efficiency.